Evaluation of Information Technology Governance Order to Cash Based on Cobit 5.0 with Domain Monitor, Evaluate and Assess (Mea 01) - Andi Kusumawati; Nurfadilah Pratiwi; Haliah Haliah (Formosa Journal of Multidisciplinary Research, 2023)
The application of technology that has become the needs and demands of the company of PT Semen Tonasa, to overcome the problem of technological implementation requires the evaluation of IT governance. The purpose of this research, in general, is to know the condition of the governance of IT order to cash specifically to know the current capability level, knowing the gap between current capability and target capability is expected, and provide the appropriate recommendation case study of PT Semen Tonasa by using the COBIT Framework 5.0 domain MEA. The data analysis method used is survey research with a quantitative descriptive approach that later results from the distribution of questionnaires will be managed to generate information in the form of figures and diagram results from the evaluation of the level of information technology governance capabilities based on the COBIT framework 5. In this study, also conducted a statistical test of T paired test, double linear regression test, and factor analysis to get a more accurate recommendation. Respondents to this research are outlined in the RACI chart according to the SAP application user in order to cash. Based on the results of the research and analysis of data conducted stated that the capability level in the MEA 01.01 sub Process (training and communication), MEA 01.02 (target responsibility and brainware quality targets), and MEA 01.03 (Measurement of responsibility and brainware quality measurement) is at level 3 or established process with a rating scale located on largely achieved. Besides, there is a comply gap in each sub-process to reach target level 4. Related to the analysis of MEA 01.04 the company needs to plan training and knowledge sharing structured, involving top management in motivating employees concerning the responsibility of SAP application use. As for the expected condition that is at level 4 (predictable process) recommended by the company is expected to make a clear design of HUMAN development measurement and make control design.